Tecniche di purificazione rituale nei papiri magici greci - Vitellozzi, Paolo (O T I V M, 2017)
As far as classical antiquity is concerned, some fundamental studies, such as Walter Burkert’s monograph on Greek religion (1977) or Robert Parker’s Miasma (1983), provide us with a clear view on the religious thoughts underlying purification rituals in the Mediterranean world. Moreover, in the past ten years, many literary and documentary sources have been collected on this topic, and they are now edited in the Thesaurus Cultus et Rituum Antiquorum. Further material regarding purification techniques in religious rituals is provided by the Greek Magical Papyri (PGM): the proposed essay deals with changes in the study of this evidence, with particular attention to the new definitions of the fields of religion and magic that have been prompted by refinements in methodology and to some aspects of the private sphere of religion in a multicultural context, such as the late imperial period.